The Southern Divide: Testing morphological differences among bifacial points from southern and southeastern Brazil using geometric morphometrics - Okumura, Mercedes; Araujo, Astolfo G. M. (Journal of Lithic Studies, 2016)
Bifacial points have been used to characterize the “Umbu” tradition in southern and southeastern Brazil. This archaeological tradition has been related to sites dated from the late Pleistocene-early Holocene boundary to near historical times. Such a huge temporal range and vast territory have suggested the existence of greater diversity within this tradition that has been ignored thus far due to the lack of systematic regional studies of such points. Through geometric morphometric analysis, this article aims to test the hypothesis that there are substantial differences in the Holocene bifacial points associated with the Umbu tradition in southeastern Brazil. Five landmarks were digitized in standardized photographs from 658 points from the states of São Paulo, Paraná, Santa Catarina, and Rio Grande do Sul. The results show that points made by groups from southeastern Brazil (São Paulo state) present a very distinct morphology (size and shape) in comparison to those made by the southern groups (Paraná, Santa Catarina and Rio Grande do Sul). This would indicate a regional identity shared only by some groups from São Paulo (at least regarding the projectile points). It is possible that Umbu tradition presents a more restricted range, both in chronological and spatial terms, than the one proposed so far.